Peningkatan Kapasitas Kader Kesehatan sebagai Mandatory Issue dalam Implementasi Peraturan Perundang-Undangan terkait Desa Siaga - Aji Perdana, Dimas; Haniyah, Haniyah (Perspektif Hukum, 2023)
One of the human rights and to fulfill other rights internationally is Health. In Indonesia, one of the constitutions, namely the 1945 Constitution Article 28 H paragraph (1), is explained regarding human rights that must be fulfilled, namely health. With the aim of maximizing health services, the government can strive for health cadres, especially for the title of alert village based on laws and regulations. This journal uses.  This research uses a type of normative juridical research using research methods of statute approach and conceptual approach. The result of this study is to show that health cadres in standby villages are mandatory laws and regulations and must be implemented so that each village can carry out comprehensive health cadre empowerment. The central government and village officials must synergize with each other so that this alert village can be formed thoroughly.